ANALISIS LIKUIDITAS DALAM MANAJEMEN PERKREDITAN PADA PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Ririn Wahyutri; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This Research is conducted in PT. Bank Riau Kepri Main Branch of Pekanbaru. Intention of this research is to know about credit management at PT. Bank Riau Kepri Main Branch of Pekanbaru as well as to know and analysis likuidity in credit management at PT. Bank of Riau Kepri Main Branch of Pekanbaru represent a calculation of balance and balance in managing credit management to determine obligation of bank in paying debt short-range to other bank.This research is descriptive quantitative. Where there is no population and sample. This study uses informance to obtain the required information. The data used is primary data and secondary data. Primary data is data obtained through interviews directly with the credit administration department and the accounting department, secondary data is information relating to research and data are already available in the company, including financial statements such as balance sheet, profit / loss, collektibility, credit, and company history organizational structure.From the analysis conducted can be seen that the calculation of cash in corporate liquidity ratio in 2010-2012 in the position of its unsanitary LDR while still in a state fluctuates in 2010 stood at a healthy enough while in 2011 and 2012 are at an unhealthy position, this is caused by the current debt ratio increased compared to its liquid instruments.Keyword : Likuidity, Collektibility, Credit Management